A test for emergent dynamics - Hook, Anson (The journal of high energy physics, 2012)
A bstract A generalization of a -maximization is proposed that maximizes a subject to inequalities rather than equalities. An implication of this conjecture is that in the absence of emergent symmetries, there is a maximum R-charge for fields appearing in the path integral. This maximum R-charge leads to a novel way of detecting emergent Abelian symmetries and non-Abelian gauge symmetries.